Produção de serapilheira e chuva de sementes no corredor de biodiversidade Santa Maria, PR - Toscan, Maria Angélica Gonçalves (2013)
This study aimed to characterize litter production and seed rain of RPPN Fazenda Santa Maria, considered a forest fragment late (FT), and to compare these indicators of ecological succession in a initial fragment (FI) and a fragment reforested (FRt). For this, were sampled nine plots of 20 x 20 m in RPPN Fazenda Santa Maria, and three of these plots were selected for the comparison of indicators of ecological succession with the other two fragments, which were also sampled three permanent plots in each. In these plots were distributed four traps of 0,5 x 0,5 m, the material deposited was collected monthly from jun/2011 to May/2012 and separated in the fractions of leaves, branches, reproductive materials and miscellaneous. From the reproductive materials the seed rain was analyzed. Among the results obtained in the characterization of RPPN Fazenda Santa Maria (FT) are the annual litterfall production of 11.886 kg.ha-1, being August and September the months of higher productions. In seed rain were collected 18,300 seeds distributed in 79 morphospecies. The months with the highest abundance of seeds were September (19%), October (20%), November (27%) and March (15%). The life form predominant was tree with 76,27% of the species, followed by climbers with 20,34% and herbaceous with 3,39%. Among the tree species, 39,02 % were represented by successional category of pioneer, while the early and late secondary categories accounted for 21,95% each and the climax 17,07%. The zoochory predominated among dispersal syndromes with 52,54%, while anemochory occurred in 38,98% and autocory in 8,47%. Already the results obtained in the comparative study of litterfall production and seed rain between the different fragments were: FT with the highest annual production (11.560 kg.ha-1), followed by FRt (9.330 kg.ha-1) and FI (7.838 kg.ha-1), but these values were not significantly different by ANOVA. In FRt were collected 7.167 seeds of 33 species and in FI 4.751 seeds of 38 species, both with predominance of seeds of pioneer and anemochoric species. In FT (RPPN Fazenda Santa Maria) were collected 2.173 seeds of 49 species, with a predominance of seeds of late secondary and climax and zoochoric species, where it was also possible to observe the asynchronism in the production of fruits by species of trees and climbers. Despite the reduction in the number of replicas which led to a reduction in the number of seeds and species, the FT fragment showed the best results among the other two. Through the characterization of litter production and seed rain, the RPPN Fazenda Santa Maria can be considered an area of forest late, with high potential for regeneration and high availability of fruit to the fauna. And with the comparative study between the two indicators, it can be observed that considering the studied areas and the number of replicas in each fragment, the seed rain was a better indicator of ecological succession in relation to litterfall production